Effect of Integrated Nutrient Management on Onion Yield and Soil Properties under Chromic haplusterts of Karnataka - P K Basavaraja; S Sridhara; A R Sushma; G R Hareesh (Journal of Horticultural Sciences, 2007)
A field experiment was conducted during the Kharif season of 2002 and 2003 under Chromic Haplusterts (medium black soils) at Zonal Agricultural Research Station, Hiriyur to study the effect of Coir Pith Based Compost (CPBC) along with organic manures and inorganic fertilizers on yield of Onion. The study revealed that combined application of CPBC @ 15 t/ha along with press mud (PM) and half the recommended dose of fertilizer (RDF) gave significant higher bulb yield of onion (14.70 t/ha) as compared to RDF along with FYM (9.55 t/ha). The bulb yields were on par with the combined application of CPBC along with FYM and 50% RDF or combined application of CPBC and Green manure (GM) along with 100% RDF, indicating the utility of CPBC in onion cultivation. Higher net and gross returns were recorded with application of CPBC and PM @ 15 t/ha each along with 50% RDF with better benefit cost ratio. The yield and quality parameters also differed significantly among the various combinations of CPBC with PM or FYM in conjunction with inorganic fertilizers. Analysis of the soil after the harvest of onion crop did not show any significant difference in pH and EC among the treatments. However, organic carbon, available phosphorus and available potash were significantly higher due to application of CPBC, PM, FYM and GM along with 50% or 100% RDF.